2017
DOI: 10.1186/s12883-017-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

Current smoking is associated with extracranial carotid atherosclerotic stenosis but not with intracranial large artery disease

Abstract: BackgroundAccumulating evidence has shown that cigarette smoking is an important risk factor for ischemic stroke. However, it is not clear about the potential mechanisms through which cigarette smoking affects stroke risk. In the study, we aimed to investigate the relationship between cigarette smoking and the occurrence of extracranial (ECAS) and intracranial atherosclerotic stenosis (ICAS).MethodsWe analyzed patients enrolled in the Chinese intracranial atherosclerosis (CICAS), which was a prospective, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
2
19
1
4
Order By: Relevance
“…A possible explanation for this finding may be due to the specific pathology of atherosclerosis in these vessel beds. Atherosclerosis in the extracranial carotid arteries is thought to be more susceptible to cigarette smoking and systemic inflammation, whereas atherosclerosis in the intracranial carotid arteries in other studies has been associated with female sex and metabolic syndrome [26][27][28][29][30]. The sex-stratified analysis did not support that mechanisms underlying intracranial artery atherosclerosis in women in general would be further aggravated in women with COPD.…”
Section: Discussionmentioning
confidence: 73%
“…A possible explanation for this finding may be due to the specific pathology of atherosclerosis in these vessel beds. Atherosclerosis in the extracranial carotid arteries is thought to be more susceptible to cigarette smoking and systemic inflammation, whereas atherosclerosis in the intracranial carotid arteries in other studies has been associated with female sex and metabolic syndrome [26][27][28][29][30]. The sex-stratified analysis did not support that mechanisms underlying intracranial artery atherosclerosis in women in general would be further aggravated in women with COPD.…”
Section: Discussionmentioning
confidence: 73%
“…In the present study, we found that genetic predisposition to smoking is associated with a 1.52-fold higher risk of LV-IS, which is consistent with some recent observational studies. For instance, a cohort study including 2656 patients with acute IS and 208 patients with transient ischemic attack found that smoking was significantly associated with the risk of extracranial atherosclerotic stenosis, which is one of the most common causes of LV-IS (OR 1.47, 95% CI 1.09–1.99) 25. However, the underlying mechanisms between smoking and LV-IS remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la dislipemia, es un factor de riesgo creciente para el desarrollo de enfermedad ateromatosa. Los datos del estudio LIPID sobre el tratamiento con estatinas muestran una reducción del riesgo de ACV de entre un 25% y el 32% en los pacientes tratados (24). La diabetes mellitus es otro factor de riesgo importante para el desarrollo de enfermedad ateromatosa.…”
Section: Discussionunclassified
“…El análisis comparativo entre factores de riesgo y sexo muestra una correlación significativa en el hábito de fumar y ser hombre. El estudio de Ruijun et al (24), establece que el hábito de fumar es un factor de riesgo asociado a la formación de estenosis carotídea extracraneal, incrementándose el riesgo en 1,1% por cada año de consumo de tabaco.…”
Section: Discussionunclassified